Restorative Justice in Criminal Procedure Reform towards a Pro Victima et Societatis System - Neng Erna Sry Denasty (Fakultas Hukum Universitas Bhayangkara Jakarta Raya, 2025)
This study aims to conduct a normative analysis of the direction of restorative justice regulations in the reform of criminal procedure law in Indonesia and the concept of restorative justice regulations in the reform of criminal procedure law that can be aligned with the principles of criminal law oriented towards victim protection and public interest. This research is motivated by the fact that the criminal justice system in Indonesia is still dominated by a retributive paradigm but often fails to achieve substantive justice. The 2025 Criminal Procedure Code draft has explicitly regulated restorative justice, but the absence of considerations regarding social impact and public unrest indicates a potential shift towards proceduralism. The research method used is normative juridical, which considers law as what is stated in legislation (law in books) with literature study and qualitative analysis methods that systematically describe secondary data. The results of the study show that the reform of criminal procedure law in Indonesia reflects a paradigm shift from retributive to restorative justice, emphasizing victim recovery, perpetrator responsibility, and social reconciliation as the objectives of punishment. Furthermore, restorative justice, which is in line with the principle of pro victima et societatis, depends on a balance between legal substance, institutional structure, and legal culture in order for the criminal justice system to be more humane and responsive to the community's need for justice